Determinants of digital technology in accounting education through the lens of unified theory of acceptance and use of technology / Irene Wee Chui Man - Irene Wee , Chui Man (2023)
Innovating teaching methods in accounting education by leveraging technology is central to support the goal line of converting accounting education to cater for the needs of today’s accounting students. This study aims to find empirical evidence to explain accounting educators’ behavioural intention and use behaviour of digital technology based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Using a quantitative approach, an online survey was administered to accounting educators working in either public or private universities in Malaysia. Partial least square (PLS), a variance-based latent variable structural equation modelling technique was used to analyse 156 valid survey and derive statistical results. The findings empirically attest the positive relation of performance expectancy, effort expectancy and social influence in enlightening the intention of accounting educators to use digital technology. Besides, behavioural intention also stands out as a critical influence on the actual use of digital technology. This study makes unique contributions to the research literature. It applies UTAUT in the accounting education context to help explicate the critical elements of the integration of digital technology for accounting educators. It also delivers insights into how UTAUT can be employed in the accounting education setting and offers ideas for boost usage of digital technology.